Overdriven Characteristics of Silica Switching Devices - Ary Syahriar; Nabil Rayhan Syahriar; Jusman Syafiie Djamal (Universitas Ahmad Dahlan, 2017)
We have built and characterized silica on silicon switching devices fabricated by using the electron beam irradiation. It is based on Mach-Zehnder structure fabricated on silica on silicon layers where the upper cladding used the MgF2 layers to bury the core. The switching speed of 2.0 s has been achieved. To further increase the switching speed we have used larger voltage to the Ti heating electrode to increase the thermo optics effects on silica structures. The higher driving voltage have been used that falls to zero exactly as the first extinction is reached, therefore three fold increase in modulation speed is achieved.